Evaluating the Effectiveness of Hybrid Project Management Approaches in Deploying Software Products Within the Banking and Financial Domain - Bindal, Anuraag (Digital Repository of Theses, 2024)
This study investigates the effectiveness of hybrid project management methodologies when deploying software solutions within the banking and financial sectors. It evaluates the strengths and limitations of both Waterfall and Agile approaches, comparing their effectiveness in managing projects in this industry. The research seeks to provide a thorough understanding of the rise of hybrid project management and its increased popularity as a solution to the complex challenges inherent in banking and financial projects. The research examines the adoption of hybrid project management through a literature review, studying its historical trajectory and current trends. The study identifies the driving factors behind its popularity and its benefits in addressing the dynamic nature of projects within the banking and financial industry. The research explores the nuances of hybrid project management, highlighting its adaptability and versatility in accommodating diverse project requirements and stakeholder expectations. The study delves into the implications of hybrid project management practices for banking and financial institutions, elucidating how these approaches facilitate enhanced collaboration, risk management, and project governance. The dissertation provides valuable insights into the strategic implications of adopting hybrid project management methodologies in the banking and financial sector by synthesizing findings from a wide range of sources, including academic literature, industry reports, and case studies. The research also examines the impact of hybrid project management on software deployment processes within banking and financial institutions. It investigates critical considerations such as integrating existing IT infrastructure, compliance with regulatory requirements, and managing project risks and uncertainties. The study analyzes empirical data and real-world examples, elucidating the role of hybrid project management in streamlining software deployment initiatives, improving operational efficiency, and driving digital transformation in the banking and financial domain. Overall, this research contributes to advancing knowledge in project management by offering a comprehensive analysis of hybrid project management practices in the banking and financial sectors. By providing actionable insights for project managers, organizational leaders, and industry practitioners, the study seeks to optimize project outcomes and enhance the delivery of software solutions in a rapidly evolving business landscape.